Laporan Kasus: Leptospirosis Berat (Weil’s Disease) dengan Manifestasi Kegagalan Multi-Organ - Anggi Kumala Rosita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to provide an understanding of leptospirosis so that diagnosis and treatment can be carried out quickly. This research method used a case study with a clinical approach, supporting examinations, and management of patients who were followed up during hospitalization. The results of this study indicate that early recognition of severe leptospirosis and comprehensive management are important factors in reducing mortality. The study concluded that healthcare professionals need to increase clinical awareness of leptospirosis in patients with fever, jaundice, and kidney disorders so that diagnosis and treatment can be initiated more quickly. Keywords: Leptospirosis, Multi-Organ Failure, Weil’s disease.